ANALISIS BALANCE SCORECARD DAN SWOT DALAM PENERAPAN KINERJA DI PERGURUAN TINGGI KESEHATAN - Jariyatin, Nurul; Bisri, Hasan (BBM (Buletin Bisnis & Manajemen), 2024)
Quality improvement Higher education does not only have good quality standards, but also needs to implement, monitor, evaluate and reward, review and update in improving performance requires scientific analysis tools to provide management thinking tools in decision making, internal and external evaluations to provide an overview of university performance comprehensively high. In this performance measurement is based on each perspective and is measured and analyzed using a quisener from the quality assurance unit, as well as using the concept of financial ratios used in measuring financial performance. Tri Darma activities that have been carried out using the SWOT analysis approach and Balanced Scorecard provide different understanding and results when using academic measures that have been carried out so far, this different understanding becomes a tool for management thinking to improve quality and quantity because Higher Education will grant academic degrees and this is very crucial if graduates do not make a good contribution in their place of work, especially in society